Hierarchical mesoporous NiFe2O4 nanocone forest directly growing on carbon textile for high performance flexible supercapacitors. Issue 22 (20th May 2016) - Javed, Muhammad Sufyan; Zhang, Cuiling; Chen, Lin; Xi, Yi; Hu, Chenguo
Abstract : The spinel phase hierarchical mesoporous NiFe2 O4 nanocone forest growing on flexible CT can offer a large number of electrochemically active sites for redox reactions. This architecture provides an ultra large exposed surface for redox reactions, short lengths for electron transfer and clear channels for electrolyte diffusion. Abstract : Binary metal oxides have been considered as promising electrode materials for high performance pseudocapacitors because they offer higher electrochemical activity than mono metal oxides. The rational design of binder free electrode architecture is an efficient solution to the further enhancement of the performance of electrochemical supercapacitors. Herein, we report the synthesis of a hierarchical mesoporous NiFe2 O4 (NFO) nanocone forest directly growing on carbon textile with ultra-high surface area by the hydrothermal method. The NiFe2 O4 nanocone forest on carbon textile (NFO-CT) was used as a binder free electrode that exhibited the high capacitance of 697 F g −1 at a scan rate of 5 mV s −1 and was further used for the fabrication of a symmetric solid state supercapacitor. The open space between hierarchical nanocones allows easy diffusion for electrolyte ions and the carbon textile ensures fast electron transfer that leads to the remarkable electrochemical performance. The NFO-CT solid state supercapacitor exhibited the high capacitance of 584 F g −1 at a scan rate of 5 mV s −1 and 93.57% capacitance retention after 10 000 cycles with the advantages of being light weight, thin and having good flexibility. A high energy density of 54.9 W h kg −1 at a power density of 300 W kg −1 was achieved, indicating the excellent energy storage features. Furthermore, three charged supercapacitors in series can light 4 red colored LEDs (2 V, 15 mA) for 2 min.